Relationship of the adherence to the Mediterranean diet with health-related quality of life and treatment satisfaction in patients with type 2 diabetes mellitus: a post-hoc analysis of a cross-sectional study - Alcubierre, Nuria (Health Qual Life Outcomes, 2016)
OBJECTIVE: The main aim of this study was to assess the association between adherence to the traditional Mediterranean diet (MedDiet) and health-related quality of life (HRQoL) and treatment satisfaction in patients with type 2 diabetes mellitus (T2DM). METHODS: This cross-sectional study included 294 patients with T2DM (146 with diabetic retinopathy and 148 without retinopathy). HRQoL and treatment satisfaction were assessed with the Audit Diabetes-Dependent Quality of Life and Diabetes Treatment Satisfaction Questionnaires, respectively. Adherence to the MedDiet was evaluated with the relative Mediterranean Diet Score (rMED). The rMED was added to multivariate linear regression models to assess its relative contribution as a quantitative as well as a qualitative variable after recoding to maximize each of the model’s coefficients of determination to explain quality of life as well as treatment satisfaction dimensions. RESULTS: The adherence to the Mediterranean diet showed no significant association with the overall quality of life score. However, rMED was associated with some HRQoL dimensions: travels, self-confidence and freedom to eat and drink (p = 0.020, p = 0.015, p = 0.037 and p = 0.015, respectively). Concerning treatment satisfaction, rMED was positively associated with its overall score (p = 0.046), and especially with the understanding of diabetes (p = 0.0004) and treatment recommendation (p = 0.036), as well as with the perceived frequency of hyperglycaemias (p = 0.039). CONCLUSION: Adherence to the Mediterranean diet was associated with greater treatment satisfaction in patients with T2DM. Although we found no association with overall HRQoL, adherence to this dietary pattern was associated with some quality of life dimensions.